Are zoo-housed collared anteaters (Tamandua tetradactyla) experiencing well-being?: seasonal assessment of basic health and serum cortisol - Busso, Juan Manuel (2017)
Zoo animal welfare is more commonly assessed based on the environment than directly measured in animals. Although most zoo-housed animals are under controlled feeding management, other environmental factors (such as temperature and photoperiod) may affect welfare measurements. Interpreting measurements without considering possible seasonal variations could thus lead to erroneous conclusions. In the present study, serum biochemistry, hematology, body weight and temperature, and serum cortisol were seasonally evaluated in 6 (3 male, 3 female) individually housed Tamandua tetradactyla from Cordoba Zoo (Argentina). Animals were exposed to natural temperature and photoperiod, and fed daily with a standard food mixture. Environmental enrichment was performed twice a week. Individual blood samples were collected in autumn (May), winter (August), spring (November) and summer (February). Considering that several wildlife studies show that glucocorticoids increase after 2-5 minutes from capture, blood was obtained before 3 minutes (physical restriction) in the morning from the coccygeal vein. Serum cortisol (ng/dL) was measured employing electrochemiluminescence immunoassay (Roche Diagnostic; previously validated). Generalized linear mixed model analysis were applied and LSD Fisher test. Seasonal changes in: creatinine (winter female: 18.1±7.4; p=0.01). This study did not reveal seasonal differences in most welfare measurements. Observed values were within the range previously reported for this species, indicating that animals were healthy throughout the study period. The serum cortisol range could be a first (gender-dependent) reference value for assessing individual wellbeing. Finally, this study contributes not only to individual health monitoring but also provides relevant information for conservation programs for these species.